2015
DOI: 10.2337/diaspect.28.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Going Mobile With Diabetes Support: A Randomized Study of a Text Message–Based Personalized Behavioral Intervention for Type 2 Diabetes Self-Care

Abstract: Objective. Patients with type 2 diabetes often fail to achieve self-management goals. This study tested the impact on glycemic control of a two-way text messaging program that provided behavioral coaching, education, and testing reminders to enrolled individuals with type 2 diabetes in the context of a clinic-based quality improvement initiative. The secondary aim examined patient interaction and satisfaction with the program.Methods. Ninety-three adult patients with poorly controlled type 2 diabetes (A1C >8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
106
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 10 publications
(9 reference statements)
0
106
0
6
Order By: Relevance
“…For example, Katz et al’s [25] 12-month intervention reported the average number of blood glucose uploads during the first and last 10 weeks of the study period, but not the full 12 months. When detailed engagement information was included, studies reported on users’ median time to respond to a text message [22, 26] and the number of users who met a minimum level of engagement (e.g., users who completed at least nine of 12 IVR calls, users who sent responses at least 3 times per week) [14, 28, 31]. Lastly, several studies categorized users by their level of engagement [21, 25, 29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Katz et al’s [25] 12-month intervention reported the average number of blood glucose uploads during the first and last 10 weeks of the study period, but not the full 12 months. When detailed engagement information was included, studies reported on users’ median time to respond to a text message [22, 26] and the number of users who met a minimum level of engagement (e.g., users who completed at least nine of 12 IVR calls, users who sent responses at least 3 times per week) [14, 28, 31]. Lastly, several studies categorized users by their level of engagement [21, 25, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, for those reporting higher engagement rates (80% and 84%), the intervention length was one [22] and three months [13], respectively. In four studies [14, 21, 23, 28], authors reported the number of users who did not engage at all or did so very minimally; rates ranged from 5.8% to 24%. In the six studies reporting changes in engagement, engagement decreased in two studies [13, 25], remained relatively stable in three studies [24, 26, 30], and varied by the individual user in one study [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost universally, published reviews have found that SMS can have a small, positive effect on health behaviors, but numerous limitations preclude definitive judgment about effectiveness. SMS behavioral interventions supporting disease self-management showed no effect on diabetes [15*] and hypertension [16*] outcomes. SMS behavioral intervention focused on improving medication adherence showed no improved adherence or health outcomes to antiretroviral therapy for HIV [17*] or naltrexone for alcohol use disorder [18*], but did show improved adherence for anti-platelet therapy in heart disease [19] and intra-nasal corticosteroids for allergic rhinitis [20].…”
Section: Is There a Role For Sms In Health Promotion?mentioning
confidence: 99%
“…To date, the majority of studies examining diabetes users' opinions of mHealth interventions have assessed helpfulness and satisfaction quantitatively with close-ended self-report scales. 14,15 Although some studies have collected qualitative feedback, study samples have been small 8,11,16 or based on a short intervention duration (i.e., 2-4 weeks). 7,17 Therefore, we conducted interviews using both quantitative and qualitative questions to understand T2DM users' experiences with and opinions of a 3-month text messaging and interactive voice response (IVR) intervention called MEssaging for Diabetes (MED).…”
Section: Introductionmentioning
confidence: 99%